Comparison of selected parameters of body composition in a group of sporting and non-sporting women - Martina Gažarová; Lucia Mečiarová; Jana Kopčeková; Mária Holovičová; Marta Habánová; Monika Bronkowska (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. Physical activity is bodily movement produced by skeletal muscle that requires energy expenditure and promotes health benefits. Appropriate physical activity is important in the prevention of cardiovascular disease, coronary heart disease, type 2 diabetes mellitus, obesity, metabolic syndrome, breast cancer, and others. Objective. The aim of the study was to compare the body composition of the selected group of women in relation to physical activity (group of sporting women (S) versus group of non-sporting women (N-S) using an InBody 230 instrument based on the principle of bioelectric impedance. Material and Methods. The group consisted of 140 women (nS = 70 vs nN-S = 70) aged 20-63 years (the average age of women doing sport was 41.1 ± 11.9 and 42.3 ± 10.87 for non-sporting women). Anthropometric measurements were made using the InBody 230 (Biospace Co. Ltd., Seoul, Republic of Korea). The Lookin'Body 3.0 software to process the results was used. The collected data concerning the anthropometric measurements were evaluated statistically and graphically in Microsoft Office Excel 2010 (Los Angeles, CA, USA). Results. The average value of BMI (Body Mass Index) of sporting women was 24.20 ± 3.54 kg.m-2 and non-sporting women 27.30 ± 5.97 kg.m-2 (PConclusions. The results of the measurements show the positive influence of physical activity on components of body composition in all age categories. Physical activity, along with rational nutrition, should be part of a healthy lifestyle for each individual.